2003
DOI: 10.1051/0004-6361:20030742
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a magnetic field in the Slowly Pulsating B starζCassiopeiae

Abstract: This gives compelling evidence for a magnetic rotator model for this star, with an unambiguous rotation period of 5.37 days. We searched for periodicity in line-profile variations (lpv), radial velocity and minimum intensity curves in the ∼400 optical spectra. We found a non-radial pulsation mode with l = 2 ± 1 at the frequency f = 0.64 c d −1 . From this periodicity and from stellar parameters derived from model fits, we propose to classify ζ Cas as a Slowly Pulsating B (SPB) star. This is the third detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 30 publications
5
95
1
1
Order By: Relevance
“…The reality of this field is now clearly confirmed by NARVAL observations . Neiner et al (2003c) reported the presence of a magnetic field in the SPB star ζ Cas = HD 3360 (still based on MuSiCoS data). Although these observations appear consistent with the presence of a field, they do not support fully convincing evidence for it.…”
Section: β Cephei Pulsators and Slowly Pulsating B Starsmentioning
confidence: 99%
“…The reality of this field is now clearly confirmed by NARVAL observations . Neiner et al (2003c) reported the presence of a magnetic field in the SPB star ζ Cas = HD 3360 (still based on MuSiCoS data). Although these observations appear consistent with the presence of a field, they do not support fully convincing evidence for it.…”
Section: β Cephei Pulsators and Slowly Pulsating B Starsmentioning
confidence: 99%
“…A field of ∼10 5 G just outside the convective core or a field of ∼10 3 G near the surface would suffice to alter modes of ν g = 10 μ Hz. The SPB star ζ Cas (Neiner et al 2003;Briquet et al 2016) exhibits a surface field slightly weaker than this and presents an interesting opportunity to study the magnetic field-pulsation interaction. Hasan et al (2005) find that a field strength of ≈10 5 G near the core will produce a ∼1% frequency splitting in SPB g-modes.…”
Section: Implications For Other Asteroseismic Targetsmentioning
confidence: 99%
“…However, for massive (non-Bp) stars, detected fields usually are dipolar (see e.g. Neiner et al 2003), a predicted behaviour for fossil fields (Braithwaite & Spruit 2004;Duez & Mathis 2010). A few nondipolar examples are known, such as τ Sco (Donati et al 2006), but they remain very rare.…”
Section: The Contribution Of the Magnetic Fieldmentioning
confidence: 99%